Mutations in CERKL and RP1 cause retinitis pigmentosa in Pakistani families - Nadeem, Raheela (Hum Genome Var, 2020)
This study was conducted to identify the genetic basis of retinal dystrophies in consanguineous Pakistani families. We recruited two families with retinitis pigmentosa (RP) displaying visual difficulties, including nyctalopia and constricted visual fields. Linkage analysis and Sanger sequencing resulted in the identification of a previously reported nonsense mutation, c.847C > T, in exon 5 of CERKL in one family and a novel four-base pair deletion in exon 4 of RP1, c.delAGAA4218_4221, leading to premature protein termination in the second family. Here, we report two RP-causing mutations extending the genetic heterogeneity of the disease.